Chinese revolution : comparative perspectives on transformation of non-western societies - Mohanty, Manoranjan 1942- (Delhi : Ajanta Publications, 1992)
Papers originally presented at an international conference held in Hangzhou, China, in November 1987.
Includes bibliographical references.
Keywords: Revolutions -- Congresses